Distribution of spontaneous inter-blink interval in repeated measurements with and without topical ocular anesthesia - Borges,Felipe Placeres (2010)
PURPOSE: To determine if the distribution of inter-blink time intervals is constant with repeated measurements with and without topical ocular anesthesia. METHODS: Inter-blink time was measured in 15 normal subjects ranging from 19 to 32 years (mean ± SD= 23.9 ± 3.20) with the magnetic search coil technique on 3 different occasions, the last one with topical ocular anesthesia. RESULTS: One-way analysis of variance for repeated measurements showed that topical anesthesia significantly reduced the blink rate (blinks per minute), which was constant in the first two measurements (F=8.27, p=0.0015. First measurement: mean ± SD= 13.7 ± 7.8; second measurement: 13.1 ± 8.5 SD; with topical anesthesia: = 7.2 ± 4.6). However, distributions shape was not affected when the blink rate was reduced. The three distributions followed a Log Normal pattern, which means that the time interval between blinks was symmetrical when the time logarithm was considered. CONCLUSIONS: Topical ocular anesthesia reduces the rate of spontaneous blinking, but does not change the distribution of inter-blink time interval.